Response Surface Methodology Research Advances and Applications - Kayarogannam, Palanikumar (IntechOpen, 2023)
Response surface methodology (RSM) is the statistical and mathematical technique that lays its foundation of quality in any experiment and it aims to optimize the response. RSM is mainly used for modeling and optimization of process parameters. This book discusses advances in RSM and its applications. Chapters discuss topics such as cyclic generators for Box-Behnken Designs, the application of RSM for product design, and potential applications of RSM in manufacturing, food processing, the fine arts, and more.